Profile of the Accuracy of Simvastatin Drug Use in the Community at BP Kulon Housing Complex, RT 02, Gresik - Maryam Hamzah, Indah (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2026)
Simvastatin is a statin drug widely used to lower blood cholesterol levels and prevent cardiovascular disease. Proper use of this drug is crucial to achieve therapeutic effectiveness and minimize the risk of side effects. This study aimed to determine the profile of simvastatin use accuracy among residents of the BP Kulon Housing Complex, RT 02, Gresik. The study used a quantitative descriptive method with a survey approach involving 65 respondents selected using a purposive sampling technique. Data were collected through a questionnaire validated through face validity testing. The results showed that the accuracy of simvastatin use based on several indicators was as follows: correct indication (76.92%), correct dosage (57.96%), correct instructions for use (30.77%), correct duration of administration (38.46%), correct route of administration (53.08%), and awareness of side effects (72.31%). The average accuracy of answers regarding simvastatin use was 57.56%. This can be concluded that the majority of residents of the BP Kulon Housing Complex, RT 02, Gresik have not fully used simvastatin correctly, especially regarding instructions for use and duration of administration.